Nalfurafine reduces neuroinflammation and drives remyelination in models of CNS demyelinating disease. Issue 1 (17th January 2021) - Denny, Lisa; Al Abadey, Afnan; Robichon, Katharina; Templeton, Nikki; Prisinzano, Thomas E; Kivell, Bronwyn M; La Flamme, Anne C
Abstract: Objectives: Multiple sclerosis (MS) is a neurodegenerative disease characterised by inflammation and damage to the myelin sheath, resulting in physical and cognitive disability. There is currently no cure for MS, and finding effective treatments to prevent disease progression has been challenging. Recent evidence suggests that activating kappa opioid receptors (KOR) has a beneficial effect on the progression of MS. Although many KOR agonists like U50, 488 are not suitable for clinical use because of a poor side‐effect profile, nalfurafine is a potent, clinically used KOR agonist with a favorable side‐effect profile. Methods: Using the experimental autoimmune encephalomyelitis (EAE) model, the effect of therapeutically administered nalfurafine or U50, 488 on remyelination, CNS infiltration and peripheral immune responses were compared. Additionally, the cuprizone model was used to compare the effects on non‐immune demyelination. Results: Nalfurafine enabled recovery and remyelination during EAE. Additionally, it was more effective than U50, 488 and promoted disease reduction when administered after chronic demyelination. Blocking KOR with the antagonist, nor‐BNI, impaired full recovery by nalfurafine, indicating that nalfurafine mediates recovery from EAE in a KOR‐dependent fashion. Furthermore, nalfurafine treatment reduced CNS infiltration (especially CD4 + and CD8 + T cells) and promoted a more immunoregulatory environment by decreasing Th17 responses. Finally, nalfurafine was able to promote remyelination in the cuprizone demyelination model, supporting the direct effect on remyelination in the absence of peripheral immune cell invasion. Conclusions: Overall, our findings support the potential of nalfurafine to promote recovery and remyelination and highlight its promise for clinical use in MS. Abstract : Nalfurafine enabled recovery and remyelination during chronic experimental autoimmune encephalomyelitis by targeting the kappa opioid receptor. Furthermore, nalfurafine reduced immune cell infiltration into the central nervous system, altered peripheral immune responses, and enabled remyelination after chronic non‐immune demyelination. Our findings support the potential of nalfurafine to promote recovery and remyelination and highlight its promise for clinical use in multiple sclerosis.